Establishment of Prognostic Nomograms for Early-Onset Prostate Cancer Patients: A SEER Database Analysis - Jingtao Li; Zhen Cai; Wei Wei; Xia Wang; Xiulan Peng (Journal of Investigative Surgery, 2022)
Objective Clinical prostate cancer (PCa) is rare in men aged <50 years (early-onset). A well-designed nomogram for prognosis prediction in patients with early-onset PCa has not been studied. Here, we tried to establish nomogram models of overall survival (OS) and cancer-specific survival (CSS) in patients with early-onset PCa. Methods The clinical variables of patients diagnosed with early-onset PCa between 2004 and 2016 were retrieved from the Surveillance, Epidemiology, and End Results (SEER) database and randomly divided into training and validation groups at a ratio of 7:3. Multivariate Cox regression analyses were used to select prognostic factors associated with OS or CSS, followed by the construction and validation of nomograms. Results We enrolled 8259 patients with early-onset PCa. New nomograms were established and showed good discriminative abilities. Finally, ROC curve analysis demonstrated that these nomograms were superior to the TNM stage and Gleason score in predicting both OS and CSS for patients with early-onset PCa. Conclusion This is the first study to establish nomograms with effective and high accuracy for prognosis in patients with early-onset PCa.